The concept of language in American media discourse on the basis of the chi-square test - Kovaliuk, Myroslava; Yesypenko, Nadiia; Pechko, Nina; Taranenko, Larysa (My University, 2023)
Language is a kind of reproduction of reality and the world of images, thanks to which a person forms and accumulates knowledge about the world picture. It (the picture of the world) can be replenished with new knowledge, corrected or regulated by human behavior. The concept of language, actualized in contemporary English-language media discourse, is an integral mental unit, the structure of which reflects the configuration of its culturally significant cognitive features that reflect the experience of language use by speakers through the prism of universal and culturally specific knowledge about language. The reflection of such a socio-cultural phenomenon as language in media discourse will help to identify the actual cognitive features of the language concept interpreted by a journalist as a representative of the American linguistic community. Linguistic and statistical methods are relevant in solving such issues of cognitive linguistics as the actualisation of nominal units by linguistic means. The use of linguistic and statistical methods in our article allows us to bring the study of the verbalization of the language image from subjective perception to the objective space of interdependence and subordination of the language system. The aim of the article is to express the concept of language using the chi-square test in American media discourse.
Keywords: language, chi-square test, quantitative analysis, lexical-semantic classes, accompanying lexeme, concept, discourse, discourse analysis